Pengembangan Lembar Kerja Peserta Didik (LKPD) Matematika Dengan Pendekatan Saintifik Untuk Sekolah Menengah Kejuruan (SMK) Negeri 2 Kota Bengkulu - Afrya Wida Safitri; Andang Sunarto; Poni Saltifa (Yayasan Darussalam Bengkulu, 2023)
This study aims to produce Mathematics Student Worksheets (LKPD) with a Scientific Approach for State Vocational High School (SMK) 2 Bengkulu City on the material of quadratic equations and functions that are valid, practical and effective. The type of research used is development research (Research and Development) with the Borg and Gall Sugiyono model. Based on the results of the product assessment from the material expert validator, the average result was 89.03% of the